Dampak Media Infografis Terhadap Pengetahuan Biopori Bagi Siswa di SMA Negeri 42 Jakarta - S, Sucahyanto; Lestariningsih, Dwi Sukanti; Rosinawati, Annisa Dwi (Peneliti.net, 2023)
Abstract: Floods are one of the most frequent disasters in Indonesia and Jakarta is the city most frequently affected by these disasters. One factor that greatly influences the frequent occurrence of floods is the lack of water catchment areas. This is caused by the number of standing buildings, the majority of which are intended for residence. One tool that can be used to overcome the problem of stagnant water that often occurs is Biopori. Biopori infiltration holes are a container or tool to reduce or prevent puddles. Research Objectives: 1) To provide knowledge to students of SMAN 42 Jakarta regarding the use of biopore infiltration holes. 2) To determine the effectiveness of infographic media. This research is a type of quantitative research using quantitative descriptive methods. The data collection technique used in the research was in the form of pretest and posttest questions. Based on the results of calculating the average pretest and posttest scores, it can be concluded that infographic media can increase the knowledge of students of SMA Negeri 42 Jakarta in biopori knowledge.